Pengaruh CAR, NPL, FDR Terhadap Profitabilitas Pada PT. Bank Muamalat Indonesia, Tbk Periode 2014-2021 - Muhammad Fajar Setyo Wicaksono; Dedi Suselo (CV ODIS, 2022)
This research was aimed at examining the influence of the Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and Financing to Deposit (FDR) on the profitability of Bank Muamalat Indonesia for the period 2014-2021. The sample of this research is the quarterly financial statements of Bank BCA Syariah for the period 2014-2021 through a purposive sampling technique. The analytical method used is multiple linear regression analysis. The results of this study indicate that partially the Effect of Capital Adequacy Ratio (CAR) has a positive and significant effect on profitability (ROA), Non-Performing Financing (NPF) has a negative and significant effect on profitability (ROA), Financing to Deposit (FDR) has a positive and significant impact on profitability. significant effect on profitability (ROA), and simultaneously CAR, NPF, and FDR have a significant and significant effect on profitability.